DIGITALIZATION BEYOND TECHNOLOGY: ORGANISATIONAL CULTURE SUSTAINABILITY AND THEIR CHANGE DUE TO THE PANDEMIC (LITERATUR REVIEW) - Roosganda Elizabeth; Martinus Tukiran; Ratu Erlina Gentari Erlinagentari; Wahyu Wiguna; Santoso Santoso; Ika Pratiwi (International Journal of Economy, Education and Entrepreneurship, 2023)
1 Technological advances and continuous digitalization are transforming an organization's resources and capabilities. Aligning with digitally oriented cultural archetypes is critical to successful digital transformation. This study aims to determine whether the Covid-19 pandemic impacts organizational culture change, as well as to find cutting-edge knowledge about productive-sustainable organizational culture and predict digital culture in organizations based on traditional cultural archetypes. The result is that the people-oriented cultural archetype is the most important for digital culture, while the values inherent in the cultural archetype of Norms or Goals inhibit it. The paper contributed to developing Functionalist and Structuralist cultural theories, showing the interaction of microcultures and cultural archetypes within an organization. Two frameworks on sustainable culture transformation and sustainability of organizational culture are derived from cutting-edge knowledge. Clean production requires managing the physical aspects of production and transforming organizational culture. What the author can criticize from these articles is the assumption that all organizations experience a decline in hierarchical culture and an increase in adhocracy culture and market culture. In fact, organizational culture shifts can vary depending on the industry, the size of the organization, and other factors